Hubungan Paritas dan Dukungan Keluarga Terhadap Pemberian Asi Eksklusif Di TPMB Mia Widana - Estu Lovita Pembayun; Rini Antika; Mira Fony Juliyanti; Nabilla Ramadhani (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Breast milk (breast milk) according to WHO is defined as the best and highly nutritious natural food or milk for babies because of its many benefits both in terms of maternal and infant. WHO also states that all children in the world have the right to breastfeed, especially in the first 6 months of life. Babies who get breast milk from the first day of birth have a smaller risk of infection, immunity because the baby's body is guaranteed, breastfeeding is proven to prevent stunting and prevent immunity reduction, but there are many obstacles and factors in the field to breastfeeding from the first day of birth such as the mother's experience in the first child, then environmental factors such as husband and family support. The purpose of this study aims to determine the relationship between postpartum maternal parity and family support for exclusive breastfeeding at TPMB Mia Widana. The research method used is quantitative with a descriptive analytical approach and cross-sectional research design. The population was 198 people, the sample used was total sampling and analyzed univariate and bivariate using the Chi square test. The results of the study showed that there was a significant relationship between the parity variable and family support for exclusive breastfeeding at TPMB Mia widana with p values of 0.000 and 0.003